Host A-to-I RNA editing signatures in intracellular bacterial and single-strand RNA viral infections - Wei, Zhi-Yuan; Wang, Zhi-Xin; Li, Jia-Huan; Wen, Yan-Shuo; Gao, Di; Xia, Shou-Yue; Li, Yu-Ning; Pan, Xu-Bin; Liu, Yan-Shan; Jin, Yun-Yun; Chen, Jian-Huan (Frontiers in Immunology, 2023)
Background Microbial infection is accompanied by remodeling of the host transcriptome. Involvement of A-to-I RNA editing has been reported during viral infection but remains to be elucidated during intracellular bacterial infections. Results Herein we analyzed A-to-I RNA editing during intracellular bacterial infections based on 18 RNA-Seq datasets of 210 mouse samples involving 7 tissue types and 8 intracellular bacterial pathogens (IBPs), and identified a consensus signature of RNA editing for IBP infections, mainly involving neutrophil-mediated innate immunity and lipid metabolism. Further comparison of host RNA editing patterns revealed remarkable similarities between pneumonia caused by IBPs and single-strand RNA (ssRNA) viruses, such as altered editing enzyme expression, editing site numbers, and levels. In addition, functional enrichment analysis of genes with RNA editing highlighted that the Rab GTPase family played a common and vital role in the host immune response to IBP and ssRNA viral infections, which was indicated by the consistent up-regulated RNA editing of Ras-related protein Rab27a. Nevertheless, dramatic differences between IBP and viral infections were also observed, and clearly distinguished the two types of intracellular infections. Conclusion Our study showed transcriptome-wide host A-to-I RNA editing alteration during IBP and ssRNA viral infections. By identifying and comparing consensus signatures of host A-to-I RNA editing, our analysis implicates the importance of host A-to-I RNA editing during these infections and provides new insights into the diagnosis and treatment of infectious diseases.